2014
DOI: 10.3389/fonc.2014.00240
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Body Radiotherapy as Treatment for Organ Confined Low- and Intermediate-Risk Prostate Carcinoma, a 7-Year Study

Abstract: Objectives: Stereotactic body radiation therapy (SBRT) takes advantage of the prostate’s low α/β ratio to deliver a large radiation dose in few fractions. Initial studies on small groups of low-risk patients support SBRT’s potential for clinical efficacy while limiting treatment-related morbidity and maintained quality of life. This prospective study expands upon prior studies to further evaluate SBRT efficacy for a large patient population with organ confined, low- and intermediate-risk prostate cancer patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
59
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(75 citation statements)
references
References 22 publications
10
59
0
6
Order By: Relevance
“…39 In terms of the development of ED following SBRT, EPIC-26 sexual domain scores appear to decrease by 5.1 points at 3 months, but rather than normalizing, they continue to decrease, with an average decrease of 7.3 points at 3 years and 13.7 points at 6 years. 35 Another study 44 found that the baseline ED rate increased from 38% to 71% after treatment but noted that more than half of the 40,41,48 have confirmed these findings, noting a stable, long-term decline in EPIC sexual scores, and ED incidence rates that depend on baseline potency and age. Mean doses to both the penile bulb and the contralateral neurovascular bundles were significantly reduced with HG plans.…”
Section: Discussionmentioning
confidence: 99%
“…39 In terms of the development of ED following SBRT, EPIC-26 sexual domain scores appear to decrease by 5.1 points at 3 months, but rather than normalizing, they continue to decrease, with an average decrease of 7.3 points at 3 years and 13.7 points at 6 years. 35 Another study 44 found that the baseline ED rate increased from 38% to 71% after treatment but noted that more than half of the 40,41,48 have confirmed these findings, noting a stable, long-term decline in EPIC sexual scores, and ED incidence rates that depend on baseline potency and age. Mean doses to both the penile bulb and the contralateral neurovascular bundles were significantly reduced with HG plans.…”
Section: Discussionmentioning
confidence: 99%
“…[5] ostre odczyny popromienne oceniane były po 3 tygodniach i 3 miesiącach od zakończenia radioterapii według skali Common Terminology Criteria for Adverse Events 4% pacjentów doświadczyło ostrych odczynów popromiennych ze strony dolnego odcinka przewodu pokarmowego i układu moczowego w stopniu 2. Nie obserwowano ostrych odczynów popromiennych w stopniu 3. ani 4.…”
Section: Omówienieunclassified
“…Стандартный курс лучевой терапии с ис-пользованием линейных ускорителей длится до 7 нед в режиме традиционного фракционирования дозы до суммарной очаговой дозы 72 Гр. Применение тех-ники гипофракционированной стереотаксической лучевой терапии позволяет сократить время лечения до 5 сеансов при подведении суммарной дозы 35 Гр (92 изоГр) [5][6][7]. Анализ отдаленных результатов лечения показал, что 5-летняя выживаемость в группе низкого риска составила 97,0 %, среднего -90,7 %, высоко-го -74,1 %.…”
Section: диагностика и лечение опухолей мочеполовой системы рак предunclassified
“…Общая 5-летняя выживаемость составила 93,0 %. Преимуществами роботизированной радиоте-рапии являются неинвазивность, безболезненность, высокая точность, максимальная доза в опухоли, ми-нимизация дозы , воздействующей на здоровые ткани, кратковременность лечения, минимальные лучевые реакции и осложнения и возможность амбулаторного лечения [6,7].…”
Section: диагностика и лечение опухолей мочеполовой системы рак предunclassified